Controlling near-field coupling for switchable metamaterial between absorption and polarization-conversion functions - Ngoc, Nguyen Van; Long, Le Van; Dzung, Dinh Ngoc; Huynh, Tran Van; Mai, Nguyen Thi; Tung, Bui Son; Khuyen, Bui Xuan; Lam, Vu Dinh (Vietnam Journal of Science and Technology, 2023)
In this paper, a multifunctional metamaterial (MM) structure capable of performing as a polarization converter and absorber is proposed. By using DC bias voltage to control the capacitor of the integrated varactor, the near-field coupling in our structure can be manipulated to flexibly switch between polarization conversion (PC) mode and perfect absorption (PA) mode. The numerical simulation results show that in PC mode the polarization conversion ratio exceeds 90 % at 4 GHz, while the dual-band absorption is observed in PA mode with a value close to 90 % at 3.5 and 5.5 GHz. In addition, we also reduce the geometric sizes of the proposed structure to further examine its performance in the THz frequency range. Owing to its excellent characteristics in both PA and PC modes, the proposed hybrid MM structure is promising to apply in many fields such as radar, remote sensing, and satellite.